2010
DOI: 10.1159/000314918
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the InVance™ Male Sling in Treating Stress Urinary Incontinence: A Three-Year Experience from a Single Centre

Abstract: Introduction: The aim of this study was to evaluate the efficacy of the InVance™ male sling in treating stress urinary incontinence. Patients and Methods: We retrospectively reviewed operative logs from a single surgeon of 43 patients treated over a 3-year period (Feb. 2004 to Nov. 2006) for stress incontinence by implantation of a male bulbourethral bone-anchoring sling (InVance™). The mean follow-up time was 24.2 months (range 4–38). Radical prostatectomy was the most common cause of incontinence in this gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
0
11
0
1
Order By: Relevance
“…Organic sling materials have been shown to degrade [16–18], and therefore synthetic mesh is now the primary material for BAS (InVance sling; American Medical Systems [AMS], Minnetonka, Minnesota, NC, USA). The degree of sling tension is an important part of this procedure, and many different methods have been reported: retrograde perfusion pressure of 30–50 cmH 2 O [18,19] or >60 cmH 2 O [20–22], cough test [16,17,22] or maximal compression with or without a urethral catheter in place [23–27]. The compressive effect of a BAS on the urethra has been shown with dynamic MRI [24].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Organic sling materials have been shown to degrade [16–18], and therefore synthetic mesh is now the primary material for BAS (InVance sling; American Medical Systems [AMS], Minnetonka, Minnesota, NC, USA). The degree of sling tension is an important part of this procedure, and many different methods have been reported: retrograde perfusion pressure of 30–50 cmH 2 O [18,19] or >60 cmH 2 O [20–22], cough test [16,17,22] or maximal compression with or without a urethral catheter in place [23–27]. The compressive effect of a BAS on the urethra has been shown with dynamic MRI [24].…”
Section: Resultsmentioning
confidence: 99%
“…It has been hypothesized that the BAS improves continence by causing a degree of urethral obstruction, and allowing better transmission of intra‐abdominal pressure to the bulbar urethra [24]. In all, 12 unique case series were identified that reported the results of bone anchored slings (Table 1) [14,16–18,20–32].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations